NOODWEER DAN NOODWEER EXCES TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN - Elvira Puspa Anggraeni; Ahmad Mahyani (Gapenas Publisher, 2022)
As a state of law, Indonesia is obliged to implement everything based on the applicable rules. No exception related to criminal acts, mistakes and also liability in accordance with applicable law. The material truth that is the value of a trial process will correlate with a person's criminal responsibility. One of them is in the case with Decision Number: 867/Pid.B/2021/PN.Jkt.Sel on behalf of the Defendant Fikri Ramadhan, who committed the murder of four FPI members in order to carry out his duties as members of the police. In order to look further into this case, the researcher formulates the problem formulation, namely how are the qualifications of noodweer and noodweer exces in criminal liability related to the crime of murder. This study uses normative legal research to find solutions to legal problems in this study. The conceptual approach and the legal approach are used by researchers as an approach method in this study. The results of this study found that Noodweer and Noodweer exces have been regulated in Article 49 of the Criminal Code. Noodweer and noodweer exces have similarities in the sense of carrying out a self-defense because of an attack that is against the law, against the body, wealth and honor of morality to either yourself or others. While between the two there is a difference, in this case the noodweer exces case there is a great mental shock experienced by the perpetrator. In the case of criminal acts in the a quo case, the murder committed by the defendant falls into the category of self-defense and self-defense that goes beyond the limits. This is because at the time of the incident the defendant experienced a very large psychological shock due to the threat of strangulation and the pointing of a firearm made by the perpetrator against the defendant and his partner, in their self-defense efforts